1998
DOI: 10.1002/(sici)1521-3773(19980202)37:1/2<164::aid-anie164>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of the First Transuranium Crown Ether Inclusion Complex: [NpO2([18]Crown-6)]ClO4

Abstract: Crown ether ligands [1,2] have been studied as potential actinide extractants for many years, and they have been shown to influence the partitioning of actinides in two-phase aqueous systems. [3±5] Although many examples of crown ether ligands that extract actinides in hydrocarbon/water systems are known, [6,7] relatively few actinide crown ether complexes in which the actinide ion is coordinated by one or more donor atoms of the crown ether have been reported. [8] There are only two inclusion compounds of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 6 publications
5
16
0
Order By: Relevance
“…As shown in Table , the calculated bond lengths are slightly overestimating both axial (for UO by about 0.022 Å) and equatorial (U–N by about 0.020–0.055 and 0.050–0.061 Å for pyrrolic and pyridine nitrogen, respectively) bonds when compared to the experimentally predicted values. A similar agreement with experiment including a slight overestimation of bond lengths has been seen before for GGA functionals such as PBE. , The calculated OUO bond angle is about 180.0°, which agrees well with the experimental value of 179.4°. It is worth mentioning that the crystal structure of the U VI O 2 L complex is characterized by a distorted hexagonal bipyramidal geometry, in agreement with the calculated gas phase structure.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As shown in Table , the calculated bond lengths are slightly overestimating both axial (for UO by about 0.022 Å) and equatorial (U–N by about 0.020–0.055 and 0.050–0.061 Å for pyrrolic and pyridine nitrogen, respectively) bonds when compared to the experimentally predicted values. A similar agreement with experiment including a slight overestimation of bond lengths has been seen before for GGA functionals such as PBE. , The calculated OUO bond angle is about 180.0°, which agrees well with the experimental value of 179.4°. It is worth mentioning that the crystal structure of the U VI O 2 L complex is characterized by a distorted hexagonal bipyramidal geometry, in agreement with the calculated gas phase structure.…”
Section: Resultssupporting
confidence: 89%
“…A similar agreement with experiment including a slight overestimation of bond lengths has been seen before for GGA functionals such as PBE. [29][30][31][32][33]35 The calculated OUO bond angle is about 180.0°, which agrees well with the experimental value of 179.4°. It is worth mentioning that the crystal structure of the U VI O 2 L complex is characterized by a distorted hexagonal bipyramidal geometry, in agreement with the calculated gas phase structure.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…That is, Sessler et al demonstrated increased covalency trends on the ligand–cation orbital interactions through structurally characterizing a series of Th­(IV)-, U­(IV)-, and Np­(IV)-containing porphyrin complexes . Clark et al pioneered the first transuranic macrocyclic complex of Np V O 2 + -18-crown-6 inclusion complex . Furthermore, Np VI O 2 2+ was proved to be stabilized within a functionalized crown ether .…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest to explore a template effect when employing organic species with restricted adaptability and fixed mutual positioning of the donor atoms. Macrocycles including crown ethers and particularly their aza derivatives seem to be the most proper candidates due to their applications in actinide partitioning [28,29], given their high selectivity for uranium [30] and neptunium [31,32]. Recently, crown ether complexes with alkali metals [33] and aza-crown ether complexes with Ni [34] were used as assemblers and linkers in uranyl-organic coordination polymers.…”
Section: Introductionmentioning
confidence: 99%